2013
DOI: 10.1111/head.12094
|View full text |Cite
|
Sign up to set email alerts
|

Epicrania Fugax: 19 Cases of an Emerging Headache

Abstract: EF appears as a distinct headache syndrome and could be eventually included in future editions of the International Classification of Headache Disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…All our patients had normal neuroimaging, but a neurovascular contact was not specifically searched with magnetic resonance angiography or MRI‐dedicated views. Otherwise, pain irradiation could be due to ephaptic transmission through different peripheral nerve fibers or to functional convergence of the trigeminal and cervical afferents at the trigeminal nucleus caudalis . The ample movement of some forms of EF with the pain crossing different structures of the face and the head would support this latter theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All our patients had normal neuroimaging, but a neurovascular contact was not specifically searched with magnetic resonance angiography or MRI‐dedicated views. Otherwise, pain irradiation could be due to ephaptic transmission through different peripheral nerve fibers or to functional convergence of the trigeminal and cervical afferents at the trigeminal nucleus caudalis . The ample movement of some forms of EF with the pain crossing different structures of the face and the head would support this latter theory.…”
Section: Discussionmentioning
confidence: 99%
“…Epicrania fugax (EF) has been recently classified as a primary headache in the appendix of the International Classification of Headache Disorders, 3rd edition, beta version . Since EF was first proposed as a new syndrome by Pareja et al in 2008, more than 60 cases have been reported . The essential feature of EF is the occurrence of dynamic painful paroxysms, with a quick and ample movement through the surface of one side of the head.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype of EF has become even broader during the last few years. For instance, it has been reported that pain paroxysms may occur at shifting sides,1,7 along the mid-sagittal plane,9 with coronal radiation10 or even in a multidirectional fashion 11. A facial variant of EF4 has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with EF present autonomic symptoms during the attacks. Interictal pain or tenderness in the stemming area is also a common feature . EF was included as a primary headache in the Appendix of the International Classification of Headache Disorders, 3rd edition, beta version (ICHD‐3 beta), among other entities pending further research .…”
Section: Introductionmentioning
confidence: 99%